2017
DOI: 10.1080/24750158.2017.1298399
|View full text |Cite
|
Sign up to set email alerts
|

Public Libraries and Access for Children with Disabilities and Their Families: A Proposed Inclusive Library Model

Abstract: and information management, university of south australia, adelaide, australia; b school of information technology and mathematical sciences, university of south australia, mawson lakes, australia; c school of education, university of south australia, mawson lakes, australia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
1
10
0
7
Order By: Relevance
“…A relevant lesson may be drawn from the perspective of South Australian research conducted by Kaeding et al (2017) on public libraries and access for children with disabilities whose special needs are not catered for in the mainstream public library services. These researchers propose an inclusive library model which is broad and encompasses the "collections, physical barriers (space and equipment), partnership, programmes, training and marketing" (p. 15).…”
Section: Inclusivity / Inclusionmentioning
confidence: 99%
“…A relevant lesson may be drawn from the perspective of South Australian research conducted by Kaeding et al (2017) on public libraries and access for children with disabilities whose special needs are not catered for in the mainstream public library services. These researchers propose an inclusive library model which is broad and encompasses the "collections, physical barriers (space and equipment), partnership, programmes, training and marketing" (p. 15).…”
Section: Inclusivity / Inclusionmentioning
confidence: 99%
“…At the same time, librarians report a need or desire for more training in the area of both autism and disability more broadly (e.g. Kaeding, Velasquez, & Price, 2017;Prendergast, 2016). The goal of this project was to address this need by developing an online autism-friendly Story Times training package for librarians.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence of this need has been raised internationally in a study of 18 librarians whose focus was on working with children with disabilities (including autism) in the US and Canada. Kaeding et al (2017) found a lack of knowledge of disability was identified as the most common barrier to access (78%), and interview data using open-ended coding of solutions to increase access similarly revealed that training of librarians was reported most frequently (39%). Simpson et al (2020) explored library access by families of preschool-age children on the autism spectrum (n = 41) and typically developing peers (n = 164; M age = 49.44 months, SD = 13.07).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying ways parents can access information regarding effective shared book reading practices within the community may provide them with a feasible alternative. and inclusive story times (Adkins and Bushman, 2015;Kaeding, Velasquez, and Price, 2017). Although such practices lay the foundations for services that support families of children with disabilities (including autism) there is little research addressing their effectiveness.…”
mentioning
confidence: 99%
“…The difficulties children who have autism may experience in accessing the library and story time sessions may be less recognised as part of their condition, with parents feeling judged for their child's behaviour (Prendergast 2016). A further barrier to delivering accessible sessions is the librarians' limited knowledge of specific disabilities (Kaeding et al, 2017).…”
mentioning
confidence: 99%